Neonatal disease environment limits the efficacy of retinal transplantation in the LCA8 mouse model. Issue 1 (December 2016) - Cho, Seo-Hee; Song, Ji; Shin, Jinyeon; Kim, Seonhee
Abstract Background Mutations of Crb1 gene cause irreversible and incurable visual impairment in humans. This study aims to use an LCA8-like mouse model to identify host-mediated responses that might interfere with survival, retinal integration and differentiation of grafted cells during neonatal cell therapy. Methods Mixed retinal donor cells (1 ~ 2 × 104 ) isolated from neural retinas of neonatal eGFP transgenic mice were injected into the subretinal space of LCA8-like model neonatal mice. Markers of specific cell types were used to analyze microglial attraction, CSPG induction and retinal cell differentiation. The positions of host retinal cells were traced according to their laminar location during disease progression to look for host cell rearrangements that might inhibit retinal integration of the transplanted cells. Results Transplanted retinal cells showed poor survival and attracted microglial cells, but CSPG was not greatly induced. Retinas of the LCA8 model hosts underwent significant cellular rearrangement, including rosette formation and apical displacement of inner retinal cells. Conclusions Local disease environment, particularly host immune responses to injected cells and formation of a physical barrier caused by apical migration of host retinal cells upon disruption of outer limiting membrane, may impose two major barriers in LCAs cell transplantation therapy.